PRNP variation in UK sporadic and variant Creutzfeldt Jakob disease highlights genetic risk factors and a novel non-synonymous polymorphism - Will Robert G; Heath Craig A; Pennington Catherine; Bishop Matthew T; Knight Richard SG (BMC, 2009)
Abstract Background Genetic analysis of the human prion protein gene (PRNP) in suspect cases of Creutzfeldt-Jakob disease (CJD) is necessary for accurate diagnosis and case classification. Previous publications on the genetic variation at the PRNP locus have highlighted the presence of numerous polymorphisms, in addition to the well recognised one at codon 129, with significant variability between geographically distinct populations. It is therefore of interest to consider their influence on susceptibility or the clinico-pathological disease phenotype. This study aimed to characterise the frequency and effect of PRNP open reading frame polymorphisms other than codon 129 in both disease and control samples sourced from the United Kingdom population. Methods DNA was extracted from blood samples and genetic data obtained by full sequence analysis of the prion protein gene or by restriction fragment length polymorphism analysis using restriction enzymes specific to the gene polymorphism under investigation. Results 147 of 166 confirmed cases of variant CJD (vCJD) in the UK have had PRNP codon 129 genotyping and all are methionine homozygous at codon 129; 118 have had full PRNP gene sequencing. Of the latter, 5 cases have shown other polymorphic loci: at codon 219 (2, 1.69%), at codon 202 (2, 1.69%), and a 24 bp deletion in the octapeptide repeat region (1, 0.85%). E219K and D202D were not found in sporadic CJD (sCJD) cases and therefore may represent genetic risk factors for vCJD. Genetic analysis of 309 confirmed UK sCJD patients showed codon 129 genotype frequencies of MM: 59.5% (n = 184), MV: 21.4% (n = 66), and VV: 19.1% (n = 59). Thirteen (4.2%) had the A117A polymorphism, one of which also had the P68P polymorphism, four (1.3%) had a 24 bp deletion, and a single patient had a novel missense variation at codon 167. As the phenotype of this latter case is similar to sCJD and in the absence of a family history of CJD, it is unknown whether this is a form of genetic CJD, or simply a neutral polymorphism. Conclusions This analysis of PRNP genetic variation in UK CJD patients is the first to show a comprehensive comparison with healthy individuals (n = 970) from the same population, who were genotyped for the three most common variations (codon 129, codon 117, and 24 bp deletion). These latter two genetic variations were equally frequent in UK sCJD or vCJD cases and a normal (healthy blood donor) UK population.